Factors affecting customer satisfaction with life insurance service quality: A case study in Hanoi - Hoang, Thanh Tung; Thao Ly, Nguyen; Hoang Anh, Le; Nguyen Nhat Anh, Doan (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to identify and evaluate factors that affect customer satisfaction in Hanoi with insurance services at a life insurance company. With 259 questionnaire survey samples, the research team used SPSS statistical software to test the research hypotheses. Research results show that 3/5 factors of service quality, including Assurance, Tangibles, and Responsiveness, positively impact customer satisfaction, while 2/5 factors, Reliability and Empathy, are not statistically significant enough to conclude the relationship affecting customer satisfaction. From the research results, the authors have proposed solutions to improve the quality of insurance services to increase customer satisfaction and promote the sustainable development of insurance businesses.